1986
DOI: 10.1002/em.2860080306
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of mutagenic propylene oxides with deoxynucleosides and DNA

Abstract: In an extension of previous studies with deoxycytidine and thymidine reactivities, propylene oxide, glycidol, epichlorohydrin, and trichloropropylene oxide were reacted with deoxyguanosine as well as deoxyadenosine and, except for the trichloro compound, with DNA. Reactivity with the purine deoxynucleosides as well as the four deoxynucleosides in DNA were quantitated by HPLC methods. Correlations were found for the reactivity with individual deoxynucleosides in solution to Taft sigma electron-withdrawing value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, there is evidence that ECH reacts with DNA, including binding covalently in vitro and in vivo (23)(24)(25)(26) as well as inducing DNA strand breaks (27,28). Studies with free bases have shown that ECH forms adducts prominently with N7 and O6 of guanine, and N6 and N3 of adenine (26,29,(30)(31)(32). Furthermore, ECH has been shown to cross-link proteins (33).…”
Section: Cross-linkers Relevant To This Studymentioning
confidence: 99%
“…However, there is evidence that ECH reacts with DNA, including binding covalently in vitro and in vivo (23)(24)(25)(26) as well as inducing DNA strand breaks (27,28). Studies with free bases have shown that ECH forms adducts prominently with N7 and O6 of guanine, and N6 and N3 of adenine (26,29,(30)(31)(32). Furthermore, ECH has been shown to cross-link proteins (33).…”
Section: Cross-linkers Relevant To This Studymentioning
confidence: 99%
“…1980;Recio et al, 19901. We have been interested in structure-mutagenicity relationships for aliphatic epoxides [Wade et a]., 1978; Neau et al, 1982;Djuric et al, 1986;Rosman et al, 19881 and have found that after in vivo exposure of mice to four aliphatic epoxides-glycidyl 1 -naphthyl cther (GNE), 1 -naphthyl propylene oxidc, glycidyl 4-nitrophenyl ether, and trichloropropylene oxide (TCPO j t h e r e were significant dose-related incrcases in the frequencies of sister-chroniatid exchanges (SCE) and chromosome aberrations (CA) in bone marrow cells for all four epoxides [Giri et al. 19893. In order to study the mechanisms of mutation by which genotoxicity was induced in the mammalian cells by cpoxides, we are determining the types, distribution, and spectra of mutations at the molecular level induced in the coding 0 1993 Wiley-Liss, Inc. region of the hypoxanthine phosphoribosyl transferase (HPRT) gene.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro 1,2-Epoxypropane binds covalently to calf thymus DNA (Djuric et al 1986;Randerath et al 1981;Solomon et al 1988). 1,2-Epoxypropane induces DNA damage and gene mutations in bacteria; it causes gene mutations in yeasts and fungi and mitotic gene conversion in Saccharomyces cerevisiae.…”
Section: Genotoxicitymentioning
confidence: 99%